Shipwreck from the 1st century BC near Cape Letavica on the island of Pag (In situ, 2025)
Research on the exceptionally well-preserved remains of a sunken ship off Cape Letavica continued in 2024, with financial support from the Ministry of Culture and Media of the Republic of Croatia. As in the previous year, the work focused on the southern part of the site, believed to be the location of the ship's galley. Among the discoveries, a fully intact amber-colored glass cup, crafted using the casting technique, stands out. Several complete or partially preserved ceramic vessels, as well as the remains of a larger metal container, were also recovered.
Keywords: ancient shipwreck; 1st century BC; amphorae of Lamboglia 2 type; glass cup; lead sheathing